Essential english for active learners : worktext for reading and language - Eusebio, Maria Fe Garcia; Zotomayor, Perla A. (Sampaloc, Manila : Rex Book Store, Inc., 2020)
"This textbook is a worktext series for Reading and Language and is anchored on the Active Learning Theory. It aims to contribute to the development of young learners into becoming mature citizens who think critically and reasonably, communicate responsibly, and love generously. Utilizing engaging and challenging learning strategies in meaningful contexts done alone or with others, the K to 12 competencies along with the 21st century skills are honed. The series is dedicated for the learners in the classroom that they may always be hopeful and eventually succeed in the future."
Includes glossary and bibliography.
English text.
Keywords: English language -- Study and teaching